5C.06: HYPERTENSION AND CARDIOVASCULAR RISK FACTORS. (June 2015) - Destro, M.; Dognini, G.P.; Pozzi, A.; Cagnoni, F.; Galimberti, V.C.; Cavalleri, C.; Besozzi, A.
Abstract : Objective: Hypertension (HT) represents the most important cardiovascular (CV) risk factor and blood pressure (BP) measurements are generally performed in medical settings, while data deriving from real life are generally poor. This work was conducted during public events out of medical setting (i.e. world hypertension day) in order to assess the prevalence of HT and evaluate other CV risk factors. Design and method: Each participating subject, after signing an informed consent, was asked to fulfil a questionnaire investigating his/her comorbidities, CV risk factors and ongoing therapies. BP measurement was performed according to the ESH/ESC guidelines. A brief counselling was then offered and brochures dealing with HT prevention provided. Results: Between May 2011 and May 2014, 1540 subjects were evaluated (mean age = 58y, median = 60y, range = 12–102y, M = 696, F = 845, M/F = 0.82). Among them, 890 (58%) declared themselves «normotensive» (mean age = 52y, median = 53y, range = 12–86, M = 408, F = 482) and 650 (42%) «hypertensive» (mean age = 65y, median = 66, range: = 22–102, M = 287, F = 363). BP measurement resulted < 140/90mmHg in 1137 subjects(=74%). Among them, 408 belonged to the «hypertensive» group, thus representing pts reaching the target pressure (=63%). On the contrary, BP > 140/90mmHg was observed in 403 subjects(=26%), 242 of them belonging to the «hypertensive» group (=non target pts) and 161 to those previously declaring «normotensive». CV risk factors were analysed, the most represented being dyslipidaemia (N = 441), smoke(N = 216), Type 2 Diabetes(N = 121), Coronary artery disease(N = 110), cerebrovascular disease(N = 44). All these risk factors were significantly more expressed in «hypertensive» pts. Number of CV risk factors was 0, 1, 2, 3, > 4 respectively for 500, 522, 312, 150, and 55 subjects. Thirty-five % of «hypertensive» pts had no other CV risk factor, but a significantly higher number of CV risk factors emerged respect to «normotensives». Conclusions: Despite the possible bias, our data provide a picture of the status of pts out of medical setting. Epidemiological data and CV risk factors were analysed, suggesting, as expected, a higher number of CV risk factors in "hypertensive" pts.